Reiche Diabetiker dürfen künftig länger leben als arme - Forst, Thomas (Der Klinikarzt, 2011)
After many years of processes, in November 2010 the decision of the Federal Joint Committee (Gemeinsamer Bundesausschuss, G-BA) to exclude glitazones from the reimbursement liability of the statutory health insurance (GKV) was no longer contradicted in the final instance by the German Ministry of Health (Bundesministerium für Gesundheit, BMG) [1]. Thereafter pioglitazone and pioglitazone-containing drugs are only liable for reimbursement by the GKV in medically-founded individual cases. This decision was based on the unfavorable cost-use profile of glitazones due to the higher risk of fractures and the occurrence of cardiac insufficiencies. This exclusion, however, is only valid for prescription of the drugs to patients with statutory health insurance in outpatient treatment. Patients with private health insurance or patients who are willing to pay for the drug themselves are of course still able to obtain pioglitazone without any problem.
Keywords: diabetes type 2; exclusion of glitazones from prescription; statutory health insurance